Mediating effect of psychological capital between the psychological load and professional identity of nursing interns (心理资本在实习护生心理负荷与职业认同间的中介效应) - LU Sheng (陆晟); WANG Zhenmeng (王振猛); SHENG Yuehong (盛月红) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the mediating effect of psychological capital between the psychological load and professional identity of nursing interns. Methods The general information questionnaire, NASA Task Load Index Scale, Psychological Capital Questionnaire and nurse Occupation Identification Scale were used to survey 292 nursing interns. Use AMOS 24. 0 software to construct a structural equation model to explore the mediating effect of psychological capital between psychological load and professional identity. Results The total score of occupational identity of nursing interns was (64. 14±10. 19). Psychological capital was positively correlated with occupational identity (r=0. 542, P<0. 01), and psychological load was negatively correlated with occupational identity (r=-0. 161, P<0. 01). Psychological capital and psychological load were negatively correlated (r=-0. 189, P<0. 01). Psychological capital played a completely intermediary role between psychological load and occupational identity, and the direct and indirect effects of psychological load on occupational identity were -0. 063 and -0. 147, respectively. Conclusion The professional identification level of interns is at a medium level, and psychological capital plays a completely intermediary role between the psychological load and professional identification. Nursing educators should take active and effective measures to reduce the psychological load of interns, pay attention to their psychological capital construction, and then enhance their professional identity. (目的 探讨心理资本在实习护生心理负荷与职业认同间的中介效应。方法 采用一般资料调查表、NASA任务负荷指数量表、心理资本问卷及护士职业认同量表对292名实习护生进行调查。采用AMOS24. 0软件构建结构方程模型, 探讨心理资本在心理负荷与职业认同间的中介效应。结果 实习护生职业认同总分为(64. 14±10. 19)分; 心理资本与职业认同呈正相关(r=0. 542, P＜0. 01), 心理负荷与职业认同呈负相关(r=-0. 161, P＜0. 01), 心理资本与心理负荷呈负相关(r=-0. 189, P＜0. 01); 心理资本在心理负荷与职业认同间起完全中介作用, 心理负荷对职业认同的直接效应与间接效应分别为-0. 063、-0. 147。结论 实习护生职业认同水平处于中等水平, 心理资本在心理负荷与职业认同间起完全中介作用。护理教育者应采取积极有效措施降低实习护生的心理负荷, 重视其心理资本建设, 进而提升职业认同感。)